Association between non-high-density lipoprotein cholesterol and type 2 diabetes: a systematic review and meta-analysis of cohort studies - Mengqi Han; Yue Shen; Xin Guo; Cheng Hong; Xincan Ji; Haoyang Guo; Yuelong Jin; Hui Yuan (Endocrine Journal)
Non-high-density lipoprotein cholesterol (non-HDL), a more readily available and reliable lipid parameter, is unclear in its association with type 2 diabetes (T2D). Previous studies assessing the relationship between non-HDL and T2D risk remains inconsistent results. We performed a meta-analysis to systematically evaluate this association. The PubMed, EMBASE, Medline, Web of Science, and Cochrane Library databases were systematically searched to find articles on “non-HDL” and “T2D” from inception to December 6, 2023. A random-effects model was used to calculate the effect estimates and 95% confidence intervals. Subgroup analyses and univariate Meta-regression were performed to explore sources of heterogeneity. The main exposure and outcome were non-HDL and T2D, respectively, in the general population. A total of 8 studies included 251,672 participants who met the inclusion criteria for this study. Meta-analysis showed that higher non-HDL increased the risk of T2D compared with the lower non-HDL group (total effect size: 1.16; 95% CI 1.079–1.251, p < 0.001). Subgroup analyses and Meta-regression of the association between non-HDL and T2D were not affected by region, proportion of men, sample size, or adjustment for confounders (including BMI, hypertension, waist circumference, and family history of diabetes). Higher non-HDL may be associated with an increased risk of T2D. Large prospective cohort studies are needed to validate these findings, and further studies are required in order to elucidate the underlying pathophysiologic mechanisms underlying the association between non-HDL and T2D.